Reverse engineering of motorcycle chain - Maleque, Md. Abdul; Rahman, Md. Mustafizur; Hossain, Sayeed (Trans Tech Publications, Switzerland, 2011)
Reverse engineering often involves taking something apart and analyzing its workings in detail to be used in maintenance or to try to make a new product or component that does the same thing without copying anything from the original. In order to understand the existing design, materials and manufacturing process of a motorcycle chain and also for the future direction in new materials with new design, a comprehensive study on the reverse engineering is essential. Therefore, in this paper, a systematic study on a motorcycle chain reverse engineering is performed. The two types of motorcycle chains (Chain A and Chain B) were destructed and investigated using the metallurgical microscope and hardness tester for microstructural and microhardness examination purposes respectively. It was found that the Chain A showed tempered martensite structure (in the case) with higher hardness value compared to Chain B. The cost analysis of the new proposed motorcycle chain is also given in this paper.